Banking sector development in a multi-currency environment: A Zimbabwean sector perspective (International Journal of Scientific Research and Management (IJSRM), 2024)
The study sought to provide an understanding of banking sector development in Zimbabwe since the introduction of the multi-currency system. This was prompted by inability of Zimbabwe’s banking system to efficiently and effectively execute its financial intermediary role of supplying affordable long-terms loans to productive sectors of the economy as a catalyst for economic growth in line with the finance-growth nexus. The study made use of an interpretivism research philosophy and utilized semi-structured interviews to gather qualitative data from a sample of fifteen senior bank executives. Study findings revealed that NPLs and thin liquidity are some of the major issues retarding the development of Zimbabwe’s banking system by creating unnecessary inefficiencies. It was also concluded that most informal business entities are using the underground economy defeating banks’ role of financial intermediation thereby curtailing banking sector development. Thus, the study recommends that banks should implement ’pay as you go’ banking models to allow bank clients to only incur costs when a service is utilized as this will motivate and attract the informal sector into using the formal banking system alleviating the liquidity position of the sector leading banking sector development and ultimately economic development.